Model komunikasi pemasaran terpadu BPJS Ketenagakerjaan Pekanbaru Panam dalam meningkatkan kepersertaan aktif segmen bukan penerima upah - Diafitri, Rahmi; Rumyeni, Rumyeni; Yozani, Ringgo Eldapi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
BPJS Ketenagakerjaan Pekanbaru Panam faces challamges in increasing the active participan of non-wage wokers (BPU), through an integrated marketing communications carried out to acquire new participanst and maintain active participation. This study uses a Qualitative method with a case study. The object of the study is to examine integrated marketing communications activities and the subject of the study are employees who are tasked with marketing the BPU program. Data were obtained through interviewa, observations and documentation. Data analysis techniques though recuction, presentation and drawing conclusions. The results of the study show that implementation of BPJS Ketenagakerjaan marketing communications includes core elements such as direct sales and management as the main account, as well as supporting elements such as advertising, publis realtions and social media. The integration of these elements creates an effevtive synergy in expanding social security protection for the BPU segment.